2023
DOI: 10.1126/scisignal.add3184
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the substrate specificity of the kinase PDK1 by distinct conformations of the full-length protein

Abstract: The activation of at least 23 different mammalian kinases requires the phosphorylation of their hydrophobic motifs by the kinase PDK1. A linker connects the phosphoinositide-binding PH domain to the catalytic domain, which contains a docking site for substrates called the PIF pocket. Here, we used a chemical biology approach to show that PDK1 existed in equilibrium between at least three distinct conformations with differing substrate specificities. The inositol polyphosphate derivative HYG8 bound to the PH do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…PDK1 activity is known to be governed by several events: (i) translocation to the plasma membrane, (ii) post-translational modifications by phosphorylation, (iii) conformational changes, and (iv) interaction with different effectors ( Sacerdoti et al, 2023 ). We demonstrated that the overactivation of PDK1 in prion-infected neurons depends on the upstream kinase ROCK ( Alleaume-Butaux et al, 2015 ).…”
Section: Ptms Of Signaling Effectors Downstream Of Prp C ...mentioning
confidence: 99%
“…PDK1 activity is known to be governed by several events: (i) translocation to the plasma membrane, (ii) post-translational modifications by phosphorylation, (iii) conformational changes, and (iv) interaction with different effectors ( Sacerdoti et al, 2023 ). We demonstrated that the overactivation of PDK1 in prion-infected neurons depends on the upstream kinase ROCK ( Alleaume-Butaux et al, 2015 ).…”
Section: Ptms Of Signaling Effectors Downstream Of Prp C ...mentioning
confidence: 99%
“…24 PIP 3 -mediated activation of PDK1 stimulates AKT phosphorylation, which subsequently inhibits a negative regulator, the tuberous sclerosis complex (TSC). 25–28 In signaling, TSC acts as the GTPase activating protein (GAP) and inhibits GTP-bound Ras homolog enriched in brain protein (RHEB, a member of the Ras superfamily). 29,30 Thus, AKT-mediated inhibition of TSC promotes RHEB activation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein phosphorylation and dephosphorylation of tyrosine, serine, and threonine are two critical enzymatic processes that control signal transduction pathways activated by growth factors, cytokines, and integrins. Kinases perform phosphorylation, while phosphatases execute hydrolysis by removing the phosphate group from phosphorylated residues. The cytoplasmic region of receptor tyrosine kinases (RTKs) includes the kinase domain and the unstructured C-terminal tail.…”
Section: Introductionmentioning
confidence: 99%